ELASTIC IMPEDANCE STUDY IN RIP AREA, GULF OF THAILAND - Wutthijuk, Penprapa (Bulletin of Earth Sciences of Thailand, 2021)
The predictions of fluvial sandstones deposited early to late Middle Miocene age, which are the main reservoirs in Pattani Basin, are always challenging. The well log data from 4 development wells and 2 exploration wells were applied with the partial-angle stacked seismic data in order to do elastic impedance inversion. Based on the rock physics analysis, the P-wave velocity does not show a good contrast for sands and shale while the density shows a significant contrast for these lithologies at all depth intervals. P-impedance shows good separation of sands and shales at the shallow section and has limitation of lithology discrimination at depth below 2000m. The crossplots of elastic impedances (near, mid and far) indicate that these can be used for lithology prediction. The far-angle elastic impedance is the best for lithology prediction and can also be used to identify the thick hydrocarbon sands in lower Middle Miocene age. The elastic impedance inversion successfully detects sands at all depths. Far-angle elastic impedance inversion effectively predicted thick hydrocarbon sands in the main reservoir interval. The elastic impedance inversion also shows good results in the case of blind-test for those wells which were not used in the inversion process. Its horizon slice successfully images the sand geometries associated with the proved reservoir distributions.